The Search for Putative Hits in Combating Leishmaniasis: The Contributions of Natural Products Over the Last Decade - Sakyi, Patrick O; Amewu, Richard K.; Devine, Robert N. O. A. (My University, 2021)
Despite advancements in the areas of omics and chemoinformatics, potent novel biotherapeutic molecules with new modes of actions are needed for leishmaniasis. The socioeconomic burden of leishmaniasis remains alarming in endemic regions. Currently, reports from existing endemic areas such as Nepal, Iran, Brazil, India, Sudan and Afghanistan, as well as newly affected countries such as Peru, Bolivia and Somalia indicate concerns of chemoresistance to the classical antimonial treatment. As a result, effective antileishmanial agents which are safe and affordable are urgently needed. Natural products from both fora and fauna have contributed immensely to chemotherapeutics and serve as vital sources of new chemical agents. This review focuses on a systematic cross-sectional view of all characterized anti-leishmanial compounds from natural sources over the last decade. Furthermore, IC50/EC50, cytotoxicity and suggested mechanisms of action of some of these natural products are provided. The natural product classification includes alkaloids, terpenes, terpenoids, and phenolics. The plethora of reported mechanisms involve calcium channel inhibition, immunomodulation and apoptosis. Making available enriched data pertaining to bioactivity and mechanisms of natural products complement current efforts geared towards unraveling potent leishmanicides of therapeutic relevance
Keywords: WACCBIP; Phenotypic screening; Leishmaniasis; Cytotoxicity; Natural products; Chemoinformatics; Chemotherapeutics; Emahi Ismaila; Whelton A. Miller; Samuel K. Kwofe; University of Ghana